Planning for growth and development - Rajavel, N. (Delhi, 2006)
This book gives the ways and means for the Growth and Development of our country. The book systematically covers various areas particular related to Higher Education including Commerce Curriculum, Tax Reformation, problem and suggestion for the tourism planning and so on. It is very useful for government authorities/agencies, planners, administrators, tour operatoers, travelling agents, tourist offices, educational instiutions, researchers, hoteliers, and all those interested in tourism and tourists.
Keywords: Planning